Konsep Pendidikan SMP Terpadu Al-Ghifari Islamic Bording School Sukabumi - Najrul Jimatul Rizki; Siti Qomariyah; Rubi Babullah; Rima Erviana; Siti Nur Afifah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The 1945 Constitution emphasizes that one of the goals of the state is to educate the life of the nation. This is relevant to the 1945 Constitution No. 20 of 2003 concerning the national education system which states that every citizen has the right to education. In this case the government is responsible for progress in national education Then, from that, various schools emerged by developing models and systems adapted to the needs of the community and the condition of the nation's children who were not free from all deficiencies in learning, both in terms of achievement and character. As a formal educational institution, the school carries out various innovations to integrate the development of character education with the Boarding School, particularly through a pesantren-based education system. One approach is through the pesantren system, which is a social institution that places great emphasis on developing students' character in addition to their academic understanding. To get to know Al-Ghifari Terpadu Islamic Boarding School further, it is a school with private status, which was founded in 1998 and is located on Jl. Selabintana KM. 6, 7, Selabatu, Sudajaya Girang, Kec. Sukabumi, Sukabumi Regency, West Java 43151. In terms of the quality of education, Al-Ghifari Integrated Middle School has been accredited “A”. and certainly has won many achievements in various championships. The method used in this research is descriptive qualitative method. Where the researcher tested the validity of the data by means of Source Triangulation, namely by conducting interviews with school heads and educators and teaching staff which was conducted on April 15 2023 and followed up with periodic communications. The findings of the researchers, in addition to getting a very extraordinary experience, the authors get various lessons out of the ordinary. Where the author knows a lot about the various education systems in it so as to increase knowledge and schools with a boarding school system are considered quite effective in building the character, character and morals of students so that they are maintained.